A Study of Prospective Teachers’ Professional Knowledge and its Practice at Secondary Level - Nawab Gul, Rabia Tabassum,Irfan Ullah (JCTE, 2023)
The study aimed to investigate the prospective teachers’ professional knowledge and its practice at secondary level and to examine the impact of different factors that affect the professional knowledge and its practice. All the 210 prospective teachers (students) of B.Ed and M.Ed, programs of Northern University Nowshera constituted population of the study. A sample of 105 prospective teachers of B.Ed and M.Ed programs were randomly selected.